Analysis The Influence of Internal Audit and Internal Control on Fraud Prevention: Literature Review Articles - Ramdhona, Muhammad Ricky; Nugrahanti, Trinandari Prasetya (Eastasouth Institute, 2024)
The objective of this study is to examine the impact of internal audit and internal control on the prevention of fraud. The used approach involves doing a literature review by examining six (6) primary studies that have investigated the impact of internal audit and inter-nal control on fraud prevention. The research findings indicate that internal audit factors have an impact on fraud prevention, while internal control variables also have an affect on fraud prevention.